Betaine alleviates scleral remodeling in experimental myopia by regulating the TLR4/TAK1/NF-κB signaling pathway - Yinqiao Zhang; Yunxiao Xie; Zhaohui Yang; Runze Gao; Shuwen Yu; Jiawen Hao; Zhongyu Ma; Yuanting Yang; Ruixue Zhang; Hongsheng Bi; Dadong Guo (Toxicology and Applied Pharmacology, 2026)

CRISPR/Cas9-mediated disruption of mdfi is associated with enhanced muscle growth in grass carp (Ctenopharyngodon idella) - Ruixue Zhang; Suxu Tan; Hongning Liu; Wenwen Wang; Yanzhao Nie; Lizheng Gao; Yiran Song; Xinlu Ren; Yu Yang; Hui Liu; Wenting Huang; Songlin Chen; et al. (Aquaculture, 2026)

Tailoring Cu-doped SmMn2O5 with rich Mn4+ active sites for highly efficient and selective ultra-low temperature photothermal NOx catalytic reduction - Mingxia Wu; Jiale Cheng; Yu Wang; Siying Zhang; Yi Li; Ruixue Bai; Chunming Yang; Lin Liu; Feng Fu; Jun Wan (Chemical Engineering Journal, 2026)

Grain quality, texture characteristics, and starch fine structure of ratoon rice practiced with high stubble height: Insights from panicles regenerated at different stem nodes - Wanfeng An; Mingji Yu; Ruixue Yu; Shuiyin Yang; Jiali Miao; Qingyao Huang; Jizhe Mu; Jianquan Qin; Chang Zheng; Xiaoyan Song; Quanzhi Zhao (Food Research International, 2026)

Cannabidiol alleviates D-galactose-induced muscle tissue aging in mice by modulating oxidative stress and is associated with alterations in gut microbiota - RuiXue Lv; Song Liu; Lili Liu; Li Yang; Meng Zhang; Shuai Li; Tianfei Yu; Ming Zhao; Xuepeng Fu; WeiWei Zhang (Food Bioscience, 2026)

Cyanobacterial relative enrichment over diatoms: Differential responses of plankton to microplastic pollution in the Zhanghe River, Northern China - Xinyue Yu; Xin Meng; Ruixue Zhao; Juan Zhang; Xiu Xu (Environmental Research, 2026)

Heteroatom-doped MXene quantum dots: red emission tuning and dual-functional performance - Fanyong Yan; Ruixue Bai; Yating Li; Shanshan Li; Jinyun Xu; Juanru Huang; Yu Wang; Yang Fu (Analytica Chimica Acta, 2026)

Peroxisome proliferator-activated receptor γ coordinates the “growth-defense trade-off” in intensive aquaculture of grass carp (Ctenopharyngodon idella) - Wenting Huang; Shaoqing Zang; Hui Liu; Xinlu Ren; Ruixue Zhang; Yu Yang; Wenwen Wang; Suxu Tan; Tingting Li; Kunpeng Shi; Zhenxia Sha (Aquaculture, 2026)

Heat-induced bovine serum albumin nanocapsules for odor masking of perilla oil - Zhili Qin; Jie Shi; Jinsong Tang; Gufen Zhang; Ruixue Huang; Chaoqun Yu (Journal of Food Engineering, 2026)

Ultrasensitive and label-free detection of piR-54265 biomarker by solution-gated graphene transistors with poly-adenine DNA assembled probe for accurate diagnosis of colorectal cancer - Tingting Yu; Peng Song; Ruixue Wang; Ziwen Chen; Liang Zhao; Ming Wang; Jianying Wang; Tao Mei; Xianbao Wang; Jinhua Li (Chemical Engineering Journal, 2026)

Genome-wide DNA methylation response of Paralichthys olivaceus to Ulva prolifera decomposition effluent stress - Yu Yang; Kunpeng Shi; Jie Ma; Mengyang Chang; Yishuai Li; Suxu Tan; Ruixue Zhang; Xinlu Ren; Xiaoyong Shi; Zhenxia Sha (Environmental Pollution, 2026)

Differential Activation of Their Cognate Receptors by NPFF and GnIH Peptides in the Half-Smooth Tongue Sole (Cynoglossus semilaevis) - Hanlin Liu; Ruixue Li; Zhihua Yu; Huapu Chen; Bin Wang (Fishes, 2026)
Neuropeptide FF (NPFF) belongs to the RF-amide peptide family and is homologous to gonadotropin-inhibitory hormone (GnIH). The NPFF precursor encodes two mature peptides, NPFF and NPAF (neuropeptide AF). Both peptides share the conserved C-terminal PQRFa motif. However, there is very limited information available on receptor cross-reactivity for NPFF and GnIH peptides in teleosts. As a first step, we cloned two cognate receptor genes for NPFF, designated as NPFFR2-1 and NPFFR2-2, in the flatfish species half-smooth tongue sole. Tissue distribution analysis revealed that npffr2-1 and npffr2-2 transcripts were present at high levels in the brain and pituitary gland, and at lower levels in some peripheral tissues. In vitro functional analysis indicated that NPFF significantly stimulated CRE-luc and SRE-luc activity in COS-7 cells expressing either NPFFR2-1 or NPFFR2-2. However, NPAF increased CRE-luc and SRE-luc activity only via NPFFR2-1. Moreover, NPFF exerted an inhibitory effect on NFAT-RE-luc activity in COS-7 cells transfected with NPFFR2-1, whereas NPAF elicited an evident stimulatory effect via NPFFR2-2. Neither GnIH1 nor GnIH2 altered CRE-luc activity in COS-7 cells transfected with NPFFR2-1 or NPFFR2-2; however, forskolin-induced CRE-luc activity was significantly reduced by these two peptides. Furthermore, neither basal nor forskolin-stimulated CRE-luc activity was modified by NPFF or NPAF in COS-7 cells expressing the GnIH receptor (GnIHR). Both GnIH1 and GnIH2 significantly increased SRE-luc activity in COS-7 cells expressing NPFFR2-1 or NPFFR2-2, and vice versa. Taken together, our findings provide novel evidence that both NPFF and GnIH peptides could exert their functions via three different receptors, and that PKA, PKC, and Ca2+ signaling pathways are potential mediators.

Investigating the Therapeutic Efficacy of Quality-Controlled, miR-146a-5p-Enriched Small Extracellular Vesicles Derived From MSCs Against Idiopathic Pulmonary Fibrosis - Xin Wang; Lingjiao Meng; Qiuhong Wang; Ruixue Rong; Yu Zhang; Xiaohui Zhao; Chen Liang; Huizhen Guo; Li Deng; Zengqi Tan; Feng Guan; Yi Tan (Stem Cell Reviews and Reports, 2026)
Small extracellular vesicles derived from umbilical cord mesenchymal stem cells (UC-sEvs) may be used for the treatment of idiopathic pulmonary fibrosis (IPF) because of their ability to control inflammation and inhibit fibrosis. However, the lack of clarity regarding the treatment mechanism of IPF and the corresponding quality standards limit the clinical application of these small extracellular vesicles. Here, we established a good manufacturing practice (GMP) grade process for isolating UC-sEvs, and RNA-seq was performed to screen for potential therapeutic cargo in the product to confirm the therapeutic effect of nebulized UC-sEv agents against IPF. Functionally, UC-sEvs inhibited the pulmonary inflammatory response by regulating macrophage function, thereby suppressing the bleomycin toxicity-induced progression of fibrosis. Mechanistically, miR-146a-5p enrichment in UC-sEvs may be involved in alleviating bleomycin-induced IPF by targeting TRAF6/IRAK1 to negatively regulate inflammation. The proposed quality control strategy ensures the stability of the product across three batches, with RNA-seq analysis revealing highly similar miRNA expression profiles. The feasibility of using miR-146a-5p as a key therapeutic molecule has been validated. Finally, on the basis of the results of pharmacodynamics and key therapeutic molecule studies, we provided a detailed quality control standard for IPF therapy by nebulizing UC-sEv. These findings help understand how sEvs impact IPF and the possible consequences of their therapeutic usage and offer a quality standard reference. Graphical Abstract

APOBEC3B-driven mutations negatively regulated by P53 promote tumor progression and immunosuppressive microenvironment in prostate cancer - Yan Guo; Haodi Yu; Xiang Li; Lina Liu; Jing He; Xin Wang; Hui Zhang; Qingyu Zhang; Jing Fu; Ruixue Gu; Hehe Li; Dengfei Xu; et al. (Molecular and Cellular Biochemistry, 2025)

Growth of cerium metal-organic framework in situ on MXene: An electrochemical sensing interface for simultaneous detection of acetaminophen and p-aminophenol - Zeyun Yang; Hao Guo; Zhiguo Yu; Lei Sun; Ruixue Yan; Wenting Niu; Jianpeng Ma; Yu Yan; Wu Yang (Journal of Environmental Chemical Engineering, 2025)

Quantitative effects of potassium application on potato tuber yield, quality, and potassium uptake in China: A meta-analysis - Fan Zhang; Xiukang Wang; Hao He; Haochen Wang; Bolun Zhang; Shiju Liu; Ruixue Chen; Yaru Zhang; Yandong Wang; Hao Ren; Yu Wang; Juan Han (Field Crops Research, 2025)

Immune-physiological responses of hemocytes to NH4Cl stress in Litopenaeus vannamei: cell death, proliferation and inflammation - Yaobing Li; Xin Yu; Ruixue Tong; Qilong Liao; Renzhi Liu; Zhengxu Chen; Luqing Pan (Fish & Shellfish Immunology, 2025)

Promoting proliferation of Lactobacillus plantarum FN107 by Dendrobium oligosaccharide-mediated elimination of carbon catabolite repression - Dongchao Xie; Ruixue Zhang; Dun Si; Jiajun Huang; Lu Wang; Jinsong Zhao; Qiaoxian Yu; Jinping Si; Jingjing Liu; Peng Jin (Carbohydrate Polymers, 2025)

Evolution analysis of key mechanical properties during the forming process of JCOE and JCOC pipes and its influence on collapse failure - Shaocong Qi; Guoyi Shen; Xihai Liu; Wanlin Cheng; Ruixue Zhai; Qingdang Meng; Jun Zhao; Gaochao Yu (Ocean Engineering, 2025)

Polymeric immunoglobulin receptor (pIgR) in cancer progression: a critical role and potential therapeutic target - Shaoju Qian; Yeqing He; Ruixue Li; Panpan Sun; Xingyi Zhang; Lin Pan; Zhishan Xu; Zhiwei Feng; Rong Lian; Lili Yu (Apoptosis, 2025)

Encapsulating boron-doped carbon dots into Eu-MOF as a ratiometric fluorescence probe for the rapid detection of caffeic acid - Yu Yan; Hao Guo; Zhiguo Yu; Zeyun Yang; Ruixue Yan; Yanyan Ma; Dengke Zhuang; Mingyue Wang; Wu Yang (Journal of Environmental Chemical Engineering, 2025)

Influence of ocean-atmosphere interactions on typhoon track and intensity: a case study for typhoon “Hato” (1713) - Yonghang Chen; Yu Wei; Yunxia Zheng; Xianwen Wu; Qiong Liu; Ruixue Li; Linlin Sun; Bingke Zhao; Sijie Yin; Haicheng Liu; Xiaoyu Li (Natural Hazards, 2025)

Impact of dropsonde data on radiation assimilation simulation for Typhoon Mujigae - Yu Wei; Yonghang Chen; Feng Wang; Bingke Zhao; Jie Tang; Qiong Liu; Zihan Zhao; Wenxin Wang; Yi Zheng; Ruixue Li (International Journal of Remote Sensing, 2025)

A study of benthic habitat classification schemes in the northern equatorial Pacific based on a Gaussian mixture model - Ranran Du; Yong Yang; Yikai Yang; Dongsheng Zhang; Ruixue Xia; Miao Yu; Gaowen He; Shuang Hong; Shengxiong Yang (Journal of Environmental Management, 2025)

Mechanisms of intestinal DNA damage and inflammation induced by ammonia nitrogen exposure in Litopenaeus vannamei - Ruixue Tong; Futao Jing; Yaobing Li; Luqing Pan; Xin Yu; Ning Zhang; Qilong Liao (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2025)

A novel dual-function fluorescence sensor Eu/CDs@MOF-808 for the sensitive detection of adenosine triphosphate and uric acid - Liping Peng; Hao Guo; Borong Ren; Yingfei Hui; Dengke Zhuang; Yu Liu; Ruixue Yan; Wenting Niu; Wu Yang (Chemical Engineering Journal, 2024)

A Q-learning based artificial bee colony algorithm for solving surgery scheduling problems with setup time - Ruixue Zhang; Hui Yu; Kaizhou Gao; Yaping Fu; Joong Hoon Kim (Swarm and Evolutionary Computation, 2024)

Genistein-3′-sodium sulfonate promotes brain functional rehabilitation in ischemic stroke rats by regulating astrocytes polarization through NF-κB signaling pathway - Ruizhen Liu; Yunling Yu; Qinglian Ge; Ruixue Feng; Guixiang Zhong; Li Luo; Zun Han; Tianyun Wang; Cheng Huang; Jinhua Xue; Zhihua Huang (Chemico-Biological Interactions, 2024)

The mechanism of reactive oxygen species generation, DNA damage and apoptosis in hemocytes of Litopenaeus vannamei under ammonia nitrogen exposure - Ruixue Tong; Yaobing Li; Xin Yu; Ning Zhang; Qilong Liao; Luqing Pan (Aquatic Toxicology, 2024)

Association Between Circulating Zinc Levels and Risk Factors of Metabolic Syndrome: Insights from a Bi-directional Mendelian Randomization Analysis and Cross-Sectional Study - Yuanyuan Wu; Guoqiong Xu; Ruixue Bai; Pingping Yu; Zhongxiang He; Mengxue Chen; Yukun Hu; Tao Jiang; Yuanhang Yang; Dongfang Liu; Ying Mei; Xiaoya Qi; et al. (Biological Trace Element Research, 2024)

Mechanisms of neurocentral-eyestalk-intestinal immunotoxicity in whiteleg shrimp Litopenaeus vannamei under ammonia nitrogen exposure - Ruixue Tong; Yaobing Li; Xin Yu; Ning Zhang; Qilong Liao; Luqing Pan (Environmental Pollution, 2024)

TDA/rGO@WS with Joule heat and photothermal synergistic effect: A promising adsorption material for all–weather recovery of viscous oil spills at sea - Min Du; Haokun Shi; Rui Yin; Jianlei Yang; Fulin Shi; Qinggong Zheng; Yu Zhou; Ruixue Guo; Wanqing Wu (Journal of Hazardous Materials, 2024)

The immunotoxicity mechanism of NH4Cl exposure to Litopenaeus vannamei based on the cerebral ganglion-eyestalk-haemocytes axis - Ruixue Tong; Yaobing Li; Xin Yu; Ning Zhang; Qilong Liao; Luqing Pan (Science of The Total Environment, 2023)

Fine and coarse particulate air pollution and out-of-hospital cardiac arrest onset: a nationwide case-crossover study in China - Chang Pan; Chang Xu; Jiaqi Zheng; Ruixue Song; Chuanzhu Lv; Guoqiang Zhang; Huiqiong Tan; Yu Ma; Yimin Zhu; Xiaotong Han; Chaoqian Li; Shengtao Yan; et al. (Journal of Hazardous Materials, 2023)

An efficient multi-task convolutional neural network for dairy farm object detection and segmentation - Fuyang Tian; Guozheng Hu; Sufang Yu; Ruixue Wang; Zhanhua Song; Yinfa Yan; Hailing Huang; Qing Wang; Zhonghua Wang; Zhenwei Yu (Computers and Electronics in Agriculture, 2023)

30 Years of Climate Change before and after the Impoundment of the Three Gorges Reservoir - Junqi Liu; Chen Lin; Shan Dong; Ruixue Feng; Aijun Su; Jinghui Cui; Shupeng Yu (Journal of Earth Science, 2023)

Development of human health criteria in China for benzo[a]pyrene: A comparison of deterministic and probabilistic approaches - Ziling Yu; Mingdeng Xiang; Ruixue Ma; Chuan Yi; Guocheng Hu; Xichao Chen; Yupei Liu; Yunjiang Yu (Chemosphere, 2023)

Hyperspectral image mixed noise removal via tensor robust principal component analysis with tensor-ring decomposition - Xiaoshuang Xu; Ruixue Gao; Yu Qing; Jun Feng; Zeyu Zeng; Maozhi Wang (International Journal of Remote Sensing, 2023)

UPLC-QTOF-MS coupled with machine learning to discriminate between NFC and FC orange juice - Ruixue Sun; Ranran Xing; Jiukai Zhang; Ning Yu; Yiqiang Ge; Weiwei Zhang; Ying Chen (Food Control, 2023)

Chronic restraint stress–induced depression-like behavior is mediated by upregulation of melanopsin expression in C57BL/6 mice retina - Yingmei Fu; Shanshan Liu; Yigang Dong; Yixia Gan; Xiaoyun Guo; Hongmei Liu; Qingqing Xu; Ruixue Yuan; Ailing Ning; Wu Hong; Yanmin Peng; Shunying Yu (Psychopharmacology, 2023)

Enhanced electrochemical performance by structural design of electrolyte surface combining 3D printing technology with multi-physical modelling - Lina Zheng; Ruixue Xu; Jinjin Zhang; Fangyong Yu; Claudia Li; Jaka Sunarso; Weimin Zhang; Xiuxia Meng; Naitao Yang (Chemical Engineering Journal, 2023)

Complete genomic sequences and comparative analysis of two Orf virus isolates from Guizhou Province and Jilin Province, China - Yanlong Zhou; Jiyu Guan; Lijun Lv; Huan Cui; Mengshi Xu; Shuai Wang; Zhaohui Yu; Ruixue Zhen; Shishi He; Ziyu Fang; Jiawei Zhong; Shanshan Cui; et al. (Virus Genes, 2022)

Response of xenobiotic biodegradation and metabolic genes in Tribolium castaneum following eugenol exposure - Yonglei Zhang; Shanshan Gao; Ping Zhang; Haidi Sun; Ruixue Lu; Runnan Yu; Yanxiao Li; Kunpeng Zhang; Bin Li (Molecular Genetics and Genomics, 2022)

TNIK influence the effects of antipsychotics on Wnt/β-catenin signaling pathway - Ruixue Yuan; Yaojing Li; Yingmei Fu; Ailing Ning; Dongxiang Wang; Ran Zhang; Shunying Yu; Qingqing Xu (Psychopharmacology, 2021)

Aristolochic acid IVa forms DNA adducts in vitro but is non-genotoxic in vivo - Jingjing Wan; Ruixue Chen; Zhou Yang; Jing Xi; Yiyi Cao; Yu Chen; Xinyu Zhang; Yang Luan (Archives of Toxicology, 2021)

Metabolomic profiling on rat brain of prenatal malnutrition: implicated for oxidative stress and schizophrenia - Fei Xu; Xin Li; Weibo Niu; Gaini Ma; Qianqian Sun; Yan Bi; Zhenming Guo; Decheng Ren; Jiaxin Hu; Fan Yuan; Ruixue Yuan; Lei Shi; et al. (Metabolic Brain Disease, 2019)

Generation of a promising universal RNAi vector system to control plant pests - Yu Pan; Yan Dong; Ruixue Wang; Minsheng Yang (Acta Physiologiae Plantarum, 2019)

Polycyclic aromatic hydrocarbons (PAHs) in multi-phases from the drinking water source area of the Pearl River Delta (PRD) in South China: Distribution, source apportionment, and risk assessment - Yunjiang Yu; Ziling Yu; Zhengdong Wang; Bigui Lin; Liangzhong Li; Xichao Chen; Xiaohui Zhu; Mingdeng Xiang; Ruixue Ma (Environmental Science and Pollution Research, 2018)

EZH2 promotes cell proliferation by regulating the expression of RUNX3 in laryngeal carcinoma - Rong Lian; Huimin Ma; Zhiyan Wu; Guozheng Zhang; Lei Jiao; Wenjie Miao; Qianqian Jin; Ruixue Li; Ping Chen; Haixu Shi; Wenfa Yu (Molecular and Cellular Biochemistry, 2018)

Performance of trichlorfon degradation by a novel Bacillus tequilensis strain PA F-3 and its proposed biodegradation pathway - Jiang Tian; Chenlei Yu; Yingwen Xue; Ruixue Zhao; Jing Wang; Lanzhou Chen (Biodegradation, 2016)

Fine mapping of a dominantly inherited powdery mildew resistance major-effect QTL, Pm1.1, in cucumber identifies a 41.1 kb region containing two tandemly arrayed cysteine-rich receptor-like protein kinase genes - Xuewen Xu; Ting Yu; Ruixue Xu; Yang Shi; Xiaojian Lin; Qiang Xu; Xiaohua Qi; Yiqun Weng; Xuehao Chen (Theoretical and Applied Genetics, 2016)

Enhancement of Cytochrome b 559 Indicates Its Possible Involvement in Long-Term High Light Stress Tolerance in Intertidal Macroalgae - Wenhui Gu; Li Huan; Ruixue Yu; Guanghua Pan; Guangce Wang (Plant Molecular Biology Reporter, 2015)

Inhibition of Proliferation of Non-small Cell Lung Cancer Cells by a bFGF Antagonist Peptide - Ruixue Wang; Wu Luo; Dan He; Jianzhang Wu; Guoxing Zhu; Xiangpeng Tan; Tao Huang; Yonglin Yu; Xiaoping Wu (International Journal of Peptide Research and Therapeutics, 2014)

A bFGF Antagonist Peptide with Anti-angiogenesis Properties in Non-small Cell Lung Cancer Cells - Ruixue Wang; Wu Luo; Xiangfeng Zeng; Jingfang Di; Yonglin Yu; Chuan Wang; Wenhui Wang; Xilei Chen; Dan He; Tao Li; Xiaoping Wu (International Journal of Peptide Research and Therapeutics, 2013)

Anti-Proliferation Effect of a Short Peptide on bFGF-Induced Human Gastric Cancer Cells - Susu Gao; Yonglin Yu; Xinqiang Lai; Tao Li; Quchou Li; Xilei Chen; Ruixue Wang; Wenhui Wang; Xiaoping Wu (International Journal of Peptide Research and Therapeutics, 2012)